Protein glycosylation in sugar beet cell line can be influenced by DNA hyper- and hypomethylating agents - Pavokovic, Dubravko; Krsnik-Rasol, Marijana (Acta Botanica Croatica, 2012)
Protein glycosylation is a co- and post-translational modification that influences protein function, stability and localization. Changes in glycoprotein pattern during differentiation/dedifferentiation events exist in animal cells and DNA methylation status is closely related to the changes. However, in plant cells this relationship is not yet established. In order to verify whether such a relation exists, hypermethylating drugs 2,4-dichlorophenoxyacetic acid and hydroxyurea, or hypomethylating drug 5-azacytozine were applied to sugar beet (Beta vulgaris L.) cells during 14 days of in vitro subculture, and the glycoprotein patterns of the cells were compared. The applied drugs were not toxic, as observed from cell phenotype and by measuring growth of the control and treated cells. Hyper and hypomethylating treatments influenced the activity of enzymes related to differentiation state of the cells: peroxidases and esterases, and their isoform patterns. Electrophoretic patterns of soluble and membrane proteins were similar between control and treatments,but the treatments modified N- and O-linked glycoprotein patterns as visible from GNAand PNAlectin blots. This suggested that hypermethylation and hypomethylation of genomic DNA in sugar beet cells affect protein glycosylation patterns and cellular metabolism, possibly in a mechanism similar to that existing in animal cells.